Influence of Permeability Anisotropy on the Seawater Intrusion Progress - Paul Emile Boka; Dogba Narcisse Dakouri; Kablan Jérôme Adou (Journal of Applied Mathematics)
In this paper, we study the influence of permeability anisotropy on the progress of the saltwater–freshwater interface in an unconfined aquifer. The model used in this study is composed of the two-phase flow equations in porous media and the transport equation of the level set function to follow the motion of the interface. We study two specific cases of permeability anisotropy, namely, the case where the main hydraulic conductivities are parallel to the axes of the reference system and the case where they are in a random reference system. We run water pumping simulations to illustrate the progress of the freshwater–saltwater interface, and we present the results.